Identified human breast milk compositions effectively inhibit SARS-CoV-2 and variants infection and replication - Xinyuan Lai; Yanying Yu; Wei Xian; Fei Ye; Xiaohui Ju; Yuqian Luo; Huijun Dong; Yi-Hua Zhou; Wenjie Tan; Hui Zhuang; Li, Tong; Xiaoyun Liu; et al. (iScience, 2022)
The global pandemic of COVID-19 caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection confers great threat to public health. Human breast milk is a complex nutritional composition to nourish infants and protect them from different kinds of infectious diseases including COVID-19. Here, we identified that lactoferrin (LF), mucin1 (MUC1), and α-lactalbumin (α-LA) from human breast milk inhibit SARS-CoV-2 infection using a SARS-CoV-2 pseudovirus system and transcription and replication-competent SARS-CoV-2 virus-like-particles (trVLP). In addition, LF and MUC1 inhibited multiple steps including viral attachment, entry, and postentry replication, whereas α-LA inhibited viral attachment and entry. Importantly, LF, MUC1, and α-LA possess potent antiviral activities toward variants such as B.1.1.7 (alpha), B.1.351 (beta), P.1 (gamma), and B.1.617.1 (kappa). Taken together, our study provides evidence that human breast milk components (LF, MUC1, and α-LA) are promising antiviral and potential therapeutic candidates warranting further development for treating COVID-19. Keywords: Biological sciences; Microbiology; Viral microbiology.